Identification and validation of a combined hypoxia and immune index for triple‐negative breast cancer. Issue 11 (1st July 2020) - Zheng, Shaoquan; Zou, Yutian; Liang, Jie‐ying; Xiao, Weikai; Yang, Anli; Meng, Tiebao; Lu, Shilin; Luo, Zhongbing; Xie, Xiaoming
Abstract : The interaction between hypoxia and immune status has been confirmed in various cancer settings, and corresponding treatments have been investigated. However, reliable biomarkers are needed for individual treatment, so we sought to develop a novel scoring system based on hypoxia and immune status. Prognostic hypoxia–immune status‐related signatures of patients with triple‐negative breast cancer (TNBC) were identified in The Cancer Genome Atlas (TCGA) ( N = 158), Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) ( N = 297), and GSE58812 ( N = 107). LASSO Cox regression was used for model construction. Hypoxia and immune status expression profiles were analyzed, and infiltrating immune cells were compared. Quantitative real‐time PCR (qRT‐PCR) was used for validation in the Sun Yat‐sen University Cancer Center (SYSUCC) cohort, and immunofluorescence was applied for the detection of hypoxia and immune markers in cancer tissues. Ten cross‐cohort prognostic hypoxia–immune signatures were included to construct the comprehensive index of hypoxia and immune (CIHI) in the METABRIC cohort. Two subgroups of patients with distinct hypoxia–immune status conditions were identified using CIHI: hypoxia high /immune low and hypoxia low /immune high, with a significantly better overall survival (OS) rate in the latter ( P < 0.01). The prognostic value of CIHI was further validated in the TCGA, GSE58812, and SYSUCC cohorts ( P < 0.01). Hypoxia–immune signatures were significantly differentially expressed between the two groups, and more active immune responses were observed in the hypoxia low /immune high group. Cytotoxic lymphocytes were inversely correlated with CIHI in silico. Differentially expressed CA‐IX and stromal PD‐L1 were detected between subgroups of the SYSUCC cohort. A hypoxia–immune‐based cross‐cohort classifier for predicting prognosis was developed and validated, which may guide hypoxia modifier treatment and immunotherapy for TNBC. Abstract : Triple‐negative breast cancer still remains a major therapeutic challenge. Efforts are underway to utilize immunotherapies in clinical practice, but not all patients benefit. Comprehensive roles of hypoxia and immune status are rarely explored. Here we construct an index from crucial signatures, indicating the relative hypoxia‐immune status. Proposed treatments might include combined hypoxia modifiers and immunotherapies.